Analysis of Labor Planning on PT. Ganda Saribu Utama Binjai - Jonner Lumban Gaol; Sarman Sinaga; Lukman Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Considering the recruitment and selection process for the company is very important to support the success of the company in achieving goals. With selective recruitment and selection will provide value for the company. The quality of the company will also improve better with competent and qualified employees. The discussion in this study is to analyze the labor planning. The results of the analysis on PT. Ganda Saribu Utama Binjai in the implementation of labor planning at PT. Ganda Saribu Utama Binjai is carried out several steps, namely: Job analysis, receiving applicant data, analyzing cover letters that have been sent to the company, conducting new employee acceptance tests, interview calls, reference examinations, and granting decisions on the acceptance of prospective new employees. And there are some obstacles that become obstacles in the company in hiring employees, which among which there are prospective employees who are dishonest, there are prospective employees who are not in accordance with the company's standards, with some obstacles, the company does things that can overcome problems in employee recruitment, starting with the implementation of selection in accordance with company procedures, and making specification adjustments in accordance with company standards.